The Unequal Effects of Globalization - Leamer, Ed (Journal of Economic Literature, 2024)
Ed Leamer of University of California, Los Angeles reviews “The Unequal Effects of Globalization” by Pinelopi Koujianou Goldberg. The Econlit abstract of this book begins: “Assesses the recent evolution of global trade, highlighting its unequal effects between and within countries.”